Psychiatric poetics: mental healthcare and Giovanni Stanghellini's ‘Logics of Discovery’ - George Ikkos; Alastair Morgan (BJPsych Bulletin)
The importance of art and humanities in mental health is widely recognised, and consumption and creation of poetry, prose, drama and the plastic arts are now considered to be relevant knowledge-generating and therapeutic activities. However, literary and art criticism remain at the margins. By contrast, in his two ‘Logics of Discovery’ papers, psychiatrist, psychopathologist and psychotherapist Giovanni Stanghellini brings to bear on clinical discovery and the healing alliance cultural historian Aby Warburg's approach to images (specifically, his Atlas of Mnemosyne) and philosopher Giorgio Agamben's analysis of the linguistic phenomenon of parataxis in Friedrich Hölderlin's poetry. Both Warburg and Hölderlin experienced severe mental disorders, and Stanghellini's analysis is notable for its potential to contribute to co-creation in a wide range of clinical settings. We suggest that this work may help to address some key sources of dissatisfaction among mental health patients and thus improve patient experience and clinical outcomes. We also comment on issues regarding implementation of Stanghellini's proposals and conclude with discussion of an example of the severe loosening of associations originally reported by Eugen Bleuler.